Folate derivative profiling and associated molecular markers in rice (Oryza sativa L.) - Cheenacharoen, Saran; Phaisansuthichol, Sirirat; Lanumteang, Krisana; Wonnapinij, Passorn; Kophimai, Yuppayao (Agriculture and Natural Resources, 2026)
Importance of the work: Folate is essential for human health, with rice being a staple food and a potential source of folate in Asia. Identifying high-folate rice varieties and developing molecular markers within genes in the folate biosynthesis pathway that are linked to folate content would support breeding for increased folate levels. Objectives: To quantify the folate content and assess the association between target molecular markers and folate levels. Materials and Methods: Folate in 65 rice samples was quantified as 5-methyltetrahydrofolate, 10-formyl folic acid, tetrahydrofolate and folic acid using high-performance liquid chromatography. Molecular markers were developed and tested for their correlation with the folate content. Results: The total folate content in the sampled rice was in the range 10.27–53.73 µg/100 g. The primary derivative found was 5-methyltetrahydrofolate. When grouped by folate content, 16 varieties with high folate levels were identified: RD14, RD21, San-Pa-Tong, Dor Kuem, Riceberry, RD10, Pathum Thani 80, Jao Daeng, Hantra 60, Niao Dtum, Homnil, Plai Ngahm Prachin Buri, Khow Yai (Purple stem), RD15, Nipponbare and RD35. Five main gene-linked molecular markers associated with folate content were identified. The microsatellite marker RM6082, located near the Aminodeoxychorismate lyase gene, was associated with the folic acid levels. Microsatellite marker RM2482, located near the Dihydroneopterin aldolase gene, was associated with the 5-methyltetrahydrofolate levels. The single nucleotide polymorphism marker within the Dihydroneopterin aldolase gene was associated with both the 10-formyl folic acid and folic acid levels. An insertion-deletion (InDel) marker within the Aminodeoxychorismate lyase gene was associated with the folic acid levels. Additionally, an InDel marker within the Dihydrofolate reductase-thymidylate synthase gene was associated with the total folate levels. Main finding: Rice varieties with high folate contents and five gene-linked molecular markers are promising candidates for breeding based on marker-assisted selection.